CT-defined visceral adipose tissue thresholds for identifying metabolic complications: a cross-sectional study in the United Arab Emirates. Issue 8 (11th August 2020) - Yoo, Sunmi; Sung, Myung-Whun; Kim, Hongdae
Abstract : Objectives: Visceral adipose tissue (VAT) is closely related to obesity complications. We aimed to determine the optimal sex-specific and age-specific VAT thresholds for predicting metabolic complications among individuals living in the United Arab Emirates (UAE). Design: Retrospective cross-sectional study. Setting: We reviewed medical records of adults who visited a hospital in the UAE. Participants: A total of 369 subjects were included in the final analysis after application of inclusion and exclusion criteria. Primary outcome measures: The prevalence of metabolic syndrome (MES). Results: MES measures excluding waist circumference were present in 73.4% of women and 78.5% of men. VAT areas adjusted for age were significantly greater in the MES group compared with the non-MES group regardless of sex (p<0.05 for all relations); however, subcutaneous adipose tissue areas adjusted for age were not significantly different. Areas under the curve used to predict MES were statistically significant for VAT and visceral to subcutaneous fat ratios among both men and women. Identified cut-off values of VAT to predict MES were 132.0 cm 2 in both sexes for individuals under the age of 50 years. For those over 50 years of age, VAT thresholds were greater in women compared with men (173 cm 2 vs 124.3 cm 2, respectively). Conclusions: Optimal VAT cut-offs to predict MES were 132 cm 2 for individuals under 50 years old living in the UAE. These measures are potential target visceral fat values that could be used to reduce obesity-related morbidity in populations with pre-existing metabolic complications.